METODE KOMUNIKASI ORANG TUA TERHADAP ANAK DALAM ISLAM (PERSPEKTIF IQ, EQ, DAN SQ) - Sunaryanto; Yulia Karmiluwati (STAI DI AL-HIKMAH, 2023)
This study aims to find out the method of parent communication in children in Islam (perspective IQ, EQ, and SQ), to find out the relationship of parent communication in children with IQ, EQ and SQ intelligence aspects and to know the application of IQ, EQ, and SQ in family and community life. The methodology used in this research is descriptive qualitative research. Primary research data obtained from literature study which is equipped with secondary data from oberservation, interview and experience of writer as consultant (trainer). The research conclusion is 1) Communication method used by parent to child in perspective IQ, EQ and SQ is Bil Hal, Bil Oral and Biblical Wisdom. 2) The relationship of parent and child communication in the perspective of IQ, EQ and SQ is the substance of Islamic teachings. With IQ, people are told to think positive things, thinking about God's power so they can be grateful for it. 3) The application of IQ, EQ, and SQ in the family are IQ, EQ, and SQ can be used in making decisions to solve various life issues, especially communication links between parents and children